Establishing PM2.5 conversion factors for South Korea at provincial level - Jasper Madalipay; Kyung Man Han; Chul H. Song; Greg Yarwood; Ross Beardsley; Swen Metzger; Jung-Hun Woo; Dogyeong Lee (Atmospheric Pollution Research, 2026)

A Review on the Benefits and Possibilities of Recirculating Aquaculture Systems (RAS) for American Lobster: Considering Environmental Response and Importance - Amélie Guitard; Benjamin de Jourdan; Noelle Babin; Carter Eagles; Atsushi Hagiwara; Jae-Seong Lee; Jeonghoon Han; Jordan Jun Chul Park (Journal of Marine Science and Engineering, 2026)
As environmental pressures intensify, sustaining ecologically and economically important marine species such as the American lobster has become an increasing challenge. Climate-driven stressors are expected to disproportionately affect early life stages of the American lobster (Homarus americanus), as sea surface temperatures are warming more rapidly than benthic habitats. In addition, environmental pollutants, including micro- and nanoplastics, trace metals, persistent organic pollutants, and per- and polyfluoroalkyl substances, can interact with climate change to exacerbate physiological stress. Previous studies have demonstrated that changes in temperature, salinity, and pH significantly influence development, moulting, cardiac function, survival, and disease susceptibility in H. americanus. In this context, aquaculture-based approaches are being explored as complementary tools to support stock resilience and reduce reliance on wild populations. Recirculating aquaculture systems (RAS) offer a controlled framework to investigate the combined effects of environmental stressors on H. americanus physiology while assessing the feasibility of closed-system rearing. Overall, this review synthesizes current knowledge on the physiological responses of H. americanus to multiple environmental stressors, with particular emphasis on identifying optimal rearing conditions in RAS. By integrating these findings, the review aims to inform strategies for improving the sustainability and long-term viability of American lobster production under changing environmental conditions.

A method for identifying revisions in ship drawings using change detection and synthetic revision generation - In-Su Han; Myung-Il Roh; Min-Chul Kong; Seong-Won Choi; Hwasup Jang; Yeonhwa Jo; Gapheon Lee (Ocean Engineering, 2026)

Combined thermal and 6PPD-quinone stressors alter biological endpoints, oxidative stress responses, and transcriptomic profiles in the rotifer Brachionus plicatilis - Amélie Guitard; Mi-Song Hong; Jae-Seong Lee; Noelle Babin; Carter Eagles; Jeonghoon Han; Chang-Bum Jeong; Jordan Jun Chul Park (Journal of Hazardous Materials, 2026)

Age Structure and Growth of the Japanese Spanish Mackerel (Scomberomorus niphonius) in Korean Waters - Han Ju Kim; Hae-young Choi; Seong Yong Moon; Hae Won Lee; Jeong-hoon Lee; Sang Chul Yoon (Fishes, 2026)
In this study, we estimated the age and growth of S. niphonius using otolith-based age determination. Five hundred and thirty individuals were sampled from commercial fisheries and the National Institute of Fisheries Science research vessels in Korean waters between January and December 2024 and from June to September 2025. Fork length ranged from 30.4 to 112.1 cm and body weight ranged from 218.2 to 9360 g. Sagittal otoliths were transversely sectioned and examined under a microscope. The age-reading precision between the two independent readers exhibited a high agreement (percentage agreement = 96.0%, average percentage error = 5.49%, coefficient of variation = 7.76%). The observed age ranges were 0–10.1 years for females and 0–8.1 years for males. Estimated parameters of the von Bertalanffy growth function were L∞=119.77 cm, K=0.41 year−1, and t0=−0.83 for females, and L∞=97.00 cm, K=0.59 year−1, and t0=−0.64 for males. Females exhibited larger asymptotic lengths but lower growth coefficients than those of males, and growth differed significantly between sexes. These results constitute the first study of age and growth based on otoliths in Korean waters and contribute to improving the biological understanding and management of this species.

Long-term spatiotemporal analysis of land surface deformation using multi-sensor InSAR in the Bangkok metropolitan area, Thailand - Gwangwoo Oh; Sooyeon Han; Yu-Chul Park; Chang-Wook Lee (Geosciences Journal, 2026)

Paraben mixture exposure and liver function in pregnant women: Findings from the Korean CHildren's ENvironmental health Study (Ko-CHENS) - Hae Ji Han; Surabhi Shah; Jongmin Oh; Yun-Chul Hong; Hwan-Cheol Kim; Kyoung Sook Jeong; Dong-Wook Lee; Yi-Jun Kim; Kyoung-Nam Kim; Kyung A Lee; Mi-Hye Park; Woo Jin Kim; et al. (Environmental Pollution, 2026)

Evaluation for the machine learning based PM2.5 estimation using different spatial resolution of geostationary satellite AOD over megacities in Korea - Juhee Lee; Jhoon Kim; Yeseul Cho; Seoyoung Lee; Drew C. Pendergrass; Daniel J. Jacob; Hyunkwang Lim; Hahn Chul Jung; Kwang-Min Myung; Young-Doh Kim; Kyung Man Han; Ja-Ho Koo (Atmospheric Environment, 2026)

Comparison of surface-guided radiotherapy-based deep inspiration breath hold and continuous positive airway pressure techniques in left-sided breast cancer: dosimetric and workflow analysis - Su Chul Han; Jason Joon Bock Lee; Jin Dong Cho; Il Sun Jeong; Heerim Nam; Hyebin Lee (Physical and Engineering Sciences in Medicine, 2026)

From Energy–Exergy optimization to improved economic and environmental performance in sustainable urea production: A comparative study of gray, blue, and green processes - Seong-Yun Bae; Eun-Uk Yu; Ankit Belbase; Min-Seo Yun; Min-Kyeong Oh; Jae-Beom Lee; Ung Lee; Hyung-Chul Yoon; Shaukat Ali Mazari; Sang-Jun Han; Jong-Ho Moon (Journal of Cleaner Production, 2026)

Boosting CO2 capture in UTSA-16 via alkali ion exchange - Hyug Hee Han; Seungho Yu; Yujin Choi; Kyu-Min Ryoum; Jong Hak Kim; Richard Blom; Carlos A. Grande; Masoud Mofarahi; Ki Chul Kim; Youn-Sang Bae (Chemical Engineering Journal, 2026)

Comparative effects of the two copper compounds: Copper chloride and copper sulfate on bioaccumulation, fecundity, and stress responses in the brine shrimp Artemia franciscana - Eunseong Lee; Chaehwan Park; Ji-Yeon Hyeon; Jordan Jun Chul Park; Kongtae Ra; Young-Ung Choi; Jeonghoon Han (Marine Pollution Bulletin, 2026)

Deactivation of Colletotrichum acutatum and Colletotrichum gloeosporioides by novel cylindrical dielectric barrier discharge plasma: Maintaining biochemical composition in strawberry by in-vitro and in-vivo - Sekar Ashokkumar; Roshani Dahal; Yung Oh Shin; Han Sup Uhm; Jang Sick Park; Young-Chul Lee; Eun Ha Choi (Food Control, 2026)

Petrogenesis of the Kalaymyo Ophiolite: Insights into mantle-melt interaction and tectonic transition from mid-ocean ridge to supra-subduction zone setting in the eastern Neo-Tethys - Gyuseung Park; Chul-Ho Heo; Sun Ki Choi; Seunghee Han; Jonguk Kim; Mi Jung Lee (Lithos, 2026)

Tailoring NO2 sensing performance of ZnO nanosheets via atmosphere-controlled annealing - Min Young Kim; Ha Eun Choa; Chul Oh. Park; Seungho Yu; Ki Chul Kim; Se Hwang Kang; Seunghyeon Yu; Gi Hyeon Han; Kyu Hyoung Lee; Yeong Min Kwon; Seung Yong Lee (Chemical Engineering Journal, 2026)

A route planning method for small ships based on historical AIS data - Seong-Won Choi; Myung-Il Roh; In-Chang Yeo; Won-Chul Yoo; Seon-Do Han (Ocean Engineering, 2026)

Magma fractionation and the magmatic-meteoric fluids mixing drive the sequential deposition of cassiterite to lepidolite in the Uljin prospects, South Korea - Ha Hyun Park; Jung Hun Seo; Bum Han Lee; Chul-Ho Heo; Marcel Guillong (Journal of Geochemical Exploration, 2026)

Dual dynamic network architecture toward circular utilization of bulk Si-based anodes for sustainable Li-ion batteries - Jin Yong Kwon; Jihong Lyu; Jin Jun Heo; Seung Hwi Han; Eunbee Kim; Hyungmin Park; Jin Chul Kim; Jaegeon Ryu (Chemical Engineering Journal, 2026)

Energy-efficient separation of cardanol, cardol, and 2-methyl cardol from biowaste using solvent extraction - Byoung Chul Kim; Woo-Seok Choi; Hyo-Bin Ryu; Su Yeong Jeong; Jeom-Soo Kim; Young Han Kim (Biomass and Bioenergy, 2026)

Corrigendum to “Hyaluronic acid wreathed, trio-stimuli receptive and on-demand triggerable nanoconstruct for anchored combinatorial cancer therapy” [Carbohydrate Polymers 249 (2020) 116815] - Kishwor Poudel; Asmita Banstola; Tuan Hiep Tran; Raj Kumar Thapa; Milan Gautam; Wenquan Ou; Le Minh Pham; Srijan Maharjan; Jee-Heon Jeong; Sae Kwang Ku; Han-Gon Choi; Chul Soon Yong; et al. (Carbohydrate Polymers, 2025)

Development of a pseudo-ternary liquid-liquid system for cardanol extraction from biowaste - Byoung Chul Kim; Woo-Seok Choi; Su Yeong Jeong; Jeom-Soo Kim; Young Han Kim (Biomass and Bioenergy, 2025)

Induction of apoptosis in pancreatic cancer cells by Albizia julibrissin extract through inhibition of an oncogenic signaling pathway - Ji Su Han; Sang-Chul Han; Seon-A Yoon; Hyejin Hyeon; Young-Min Ham; Yong-Hwan Jung; Hye-Jin Boo (Phytochemistry Letters, 2025)

An extract of Boehmeria nivea induces apoptosis by disrupting oncogenic signaling in human pancreatic cancer cells - Sang-Chul Han; Ji Su Han; Seon-A Yoon; Hyejin Hyeon; Young-Min Ham; Yong-Hwan Jung; Hye-Jin Boo (Phytochemistry Letters, 2025)

Utilization of oxided tamarind polysaccharide gum as novel selective depressant in the flotation separation of copper-lead-zinc sulfide ore - Tichen Wang; Jiushuai Deng; Hao Zhang; Dingquan Xing; Zhiguo Han; Jie Sheng; Chul B. Park (Process Safety and Environmental Protection, 2025)

Oxidative modification and structural characterization of konjac gum and its effect on the flotation separation of chalcopyrite from galena - Tichen Wang; Jiushuai Deng; Dingquan Xing; Zhiguo Han; Yue Gao; Qizheng Qin; Hao Zhang; Hongxiang Xu; Chul B. Park (Journal of Cleaner Production, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Prediction of enthalpy of vaporization for particulate matter through molecular dynamics using OPLS force field - Seung Weon Jeong; Yeonseo Kim; Hyung-Kyu Lim; Min Chan Kim; Chul Han Song; Sangheon Lee (Journal of Aerosol Science, 2025)

In silico screening of epitopes as potential vaccine candidates against pathogenic Acinetobacter baumannii - Md. Minarul Islam; Kyudong Han; Ye-Ji Bang; Je Chul Lee; Woo Shik Shin; Man Hwan Oh (Genes & Genomics, 2025)

Long-term exposure to air pollution and incident Alzheimer’s disease among older adults: evidence from a large-scale retrospective cohort in Korea - Hyung Doo Kim; Jongmin Oh; Jisun Myung; Changwoo Han; Hyun Joo Bae; Soontae Kim; Yun-Chul Hong; Youn-Hee Lim; Dong-Wook Lee (Environmental Science and Pollution Research, 2025)

Improved estimation of new particle formation rate for air quality model in a polluted region of South Korea - Yusin Kim; Sangdeok Shim; Seogju Cho; Seong Soo Yum; Chul Han Song; Sung Hoon Park (Atmospheric Environment, 2025)

A representation method of pipe connections and routing space in pipe auto-routing using graph and octree structures - Min-Chul Kong; Myung-Il Roh; In-Su Han; Inseok Lee; Hyunseung Lee; Mijin Kim; Jeoungyoun Kim; Jinhyeong You (Ocean Engineering, 2025)

Acute toxicity of antifouling agents CuSO4, ZnPT, and CuPT on marine diatoms Skeletonema costatum and Navicula sp. - Taesoo Kim; Huijeong Byeon; Yunji An; Vijay Rayamajhi; Jihyun Lee; Jong Dae Lee; Kwang Soo Lee; Chul-Hyun Kim; Juwon Oh; Jung Han Park; Hyun Woung Shin; Sang Mok Jung (Marine Environmental Research, 2025)

The effects of blending diisopropanolamine and 2-amino-2-methyl-1-propanol for carbon dioxide capture process: Comparative study using thermodynamic modeling and artificial neural network predictions - Hail Sung; Sung-Chul Han; Pil Rip Jeon; Kyung-Min Kim (Journal of Cleaner Production, 2025)

Species identification of the rotifer Brachionus plicatilis sp. complex used in Japanese hatcheries and the implications for application - Chengyan Han; Shohei Kamizono; Yoshitaka Sakakura; Min-Sub Kim; Min-Chul Lee; Jae-Seong Lee; Atsushi Hagiwara (Fisheries Science, 2025)

Enhancing indigenous plant growth in metal(loid) contaminated soil using biochar - Han Na Kim; Keum Chul Yang; Su Kyeong Shin; Yeong Ju Seok; Ju-Sung Cho; Hyo Kyung Jee; Jeong Yeon Kim; Jin Hee Park (Chemosphere, 2025)

Neurotoxic effects of citronellol induced by the conversion of kynurenine to 3-hydroxykynurenine - Seong Soon Kim; Suhyun Kim; Yeonhwa Kim; Youngran Ha; Hyojin Lee; Hyunji Im; Jung Yoon Yang; Dae-Seop Shin; Kyu-Seok Hwang; Yuji Son; Sung Bum Park; Ki Young Kim; et al. (Journal of Hazardous Materials, 2025)

Effects of temperature changes on oxidative stress and antioxidant defense system in the Zhikong scallop Chlamys farreri - Jin Ah Song; Eunseong Lee; Young-Ung Choi; Jordan Jun Chul Park; Jeonghoon Han (Fisheries Science, 2025)

Damage localization using low-frequency bridge acceleration component under a moving vehicle - Xuzhao Lu; Limin Sun; Kai-Chun Chang; Chul-Woo Kim; Zhuoran Han (Engineering Structures, 2025)

Efficient radon removal using a metal–organic framework with high density of unsaturated Co2+ sites - Kwang Hyun Oh; Seungho Yu; Jung Sub Kim; Kijun Kim; Hyug Hee Han; Yujin Choi; Ki Chul Kim; Youn-Sang Bae (Chemical Engineering Journal, 2025)

5-Fluorouracil induces hair loss by inhibiting β-catenin signaling and angiogenesis - Jung-Il Kang; Youn Kyung Choi; Sang-Chul Han; Jin Won Hyun; Young-Sang Koh; Jaeseong Oh; Hye-Jin Boo; Eun-Sook Yoo; Hee-Kyoung Kang (Chemico-Biological Interactions, 2025)

Population genetics analysis based on mitochondrial cytochrome c oxidase subunit I (CO1) gene sequences of Cottus koreanus in South Korea - Bong Han Yun; Yong Hwi Kim; Ho-Seop Han; In-Chul Bang (Genes & Genomics, 2025)

Quantitative Real-Time Polymerase Chain Reaction (PCR) Assay for Rapid Monitoring of the Harmful Algal Bloom Species Cochlodinium polykrikoides - Min-Jeong Kim; Hyun-Jung Kim; Joon Sang Park; Donhyug Kang; Sungho Cho; Hansoo Kim; Seung Ho Baek; Jordan Jun Chul Park; Jeonghoon Han; Kang Eun Kim; Seung Won Jung (Journal of Marine Science and Engineering, 2025)
Harmful blooms of the dinoflagellate Cochlodinium polykrikoides (Margalefidinium polykrikoides) had detrimental aquacultural and economic effects globally, and to reduce the damage caused by these blooms, early biomonitoring and quantitative analysis of C. polykrikoides are of the utmost importance. Here, for the detection of C. polykrikoides using quantitative real-time polymerase chain reactions, we developed specific primers targeting the large subunit ribosomal DNA (LSU rDNA) and evaluated their applicability in the field during the occurrence of a C. polykrikoides bloom. The specific primers not only accurately detected C. polykirkoides but also had a detection performance comparable with that obtained using microscopic observations. Accordingly, we developed a system that can be used in the field and applied when red tides occur, with accurate results being obtained more than five times more rapidly than those obtained based on microscopic analysis. Collectively, our findings indicate that the C. polykrikoides bloom detection system developed in this study can be applied to rapidly detect and accurately quantify C. polykrikoides in environmental samples. Data obtained using this system could be used as a basis for developing prompt monitoring and warning systems for the early detection of C. polykrikoides blooms in the field.

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Trends and classification of aerosol observed from MODIS sensor over Northern Europe and the Arctic - Kyung M. Han; Chang H. Jung; Chul H. Song; Ja H. Koo; Young J. Yoon; Bang Y. Lee; Hyun S. Kim; S. Seo (Atmospheric Pollution Research, 2025)

Bacterial profile-based body fluid identification using a machine learning approach - Sungmin Kim; Han Chul Lee; Jeong Eun Sim; Su Jeong Park; Hye Hyun Oh (Genes & Genomics, 2025)

The photosynthetic uptake of inorganic carbon from Pyropia seaweed aquaculture beds: Scaling up population-level estimations - Ju-Hyoung Kim; Hanbi Moon; Mi-Jung Han; Ji Eun Jung; Na Young Lee; Jin Woo Kang; Ji Chul Oh; Geun-Ha Park; Seon-Eun Lee; Myoung Hoon Lee; Chae-Un Park; Ho-Sung Yoon; et al. (Aquaculture, 2024)

Validation of analytical methods for newly regulated veterinary drug residues in livestock and fishery products with maximum residue limits in Republic of Korea - Dahae Park; Sang Beom Han; Ho-Chul Shin; Yong Seok Choi; Yu Ra Kim; Ji Young Kim; Gui-Hyun Jang; Miok Eom (Food Chemistry, 2024)

Exosomal miR-196b secreted from bronchial epithelial cells chronically exposed to low-dose PM2.5 promotes invasiveness of adjacent and lung cancer cells - Seong-Lan Yu; Han Koo; Yujin Kang; Hye Jin Jeon; Minho Kang; Dong Hee Choi; Su Yel Lee; Ji Woong Son; Dong Chul Lee (Toxicology Letters, 2024)

Green process for Polyurethane: From CO2 to isocyanate - Jung Ae Lim; Young-Woo You; Seung Kwon Kang; Jongseon Rho; Suyeon Yeo; Seulgi Han; Mintaek Im; Un Young Kim; Min-Chul Kim; Tae-Sun Chang; Ji Hoon Park; Jinjoo An; et al. (Chemical Engineering Journal, 2024)

Field demonstration of a 10 MW CO2 capture pilot plant in extended operation using KoSol absorbents for treating off-gas in a coal fired power plant - No-Sang Kwak; Jinkyu Jung; Junghyun Lee; Sung-Chul Han; Jae-Goo Shim; Kyung-Min Kim; Doh C. Lee (International Journal of Greenhouse Gas Control, 2024)

Deep-BCSI: A deep learning-based framework for bias correction and spatial imputation of PM2.5 concentrations in South Korea - Deveshwar Singh; Yunsoo Choi; Jincheol Park; Ahmed K. Salman; Alqamah Sayeed; Chul Han Song (Atmospheric Research, 2024)

Enhancement of denitrification by sulfur-based carrier in sequencing batch reactor (SBR) for advanced wastewater treatment - Cheol-Gyu Park; Jin-San Lee; Sun-A An; Seong-Min Cho; Inhong Min; Yun Chul Woo; Han-Seung Kim (Chemosphere, 2024)

Development of Biological Risk Assessment Protocols for Evaluating the Risks of In-Water Cleaning of Hull-Fouling Organisms - Bonggil Hyun; Pung-Guk Jang; Min-Chul Jang; Jung-Hoon Kang; Ju-Hyoung Kim; Jang-Seu Ki; Dong Han Choi; Ok Hwan Yu; Jin-Young Seo; Woo-Jin Lee; Kyoungsoon Shin (Journal of Marine Science and Engineering, 2024)
Herein, we evaluate the scientific basis for managing hull fouling of ships entering Korean ports, diagnose biological risks that may occur when in-water cleaning (IWC) systems remove hull fouling, and present a protocol for evaluating these risks (the Korean Infection Modes and Effects Analysis; K-IMEA). Protocol development included the selection of core elements and scenario design for IWC and the evaluation of regrowth experiments. The K-IMEA index was designed by considering the inoculation pathway of attaching organisms in all processes to ships that enter a port for in-water cleaning. A number of risk indices were defined: R1—Introduction/Establishment of alien species before in-water cleaning; R2—Establishment of alien species escaped during in-water cleaning; R3—Introduction/Establishment of alien species after in-water cleaning; and R4—Establishment of alien species in effluent water. K-IMEA regrowth experiments (R2 and R4) using the in-water cleaning effluent showed that the attachment and regrowth of prokaryotes, microalgae, and macroalgae were successfully detected. In particular, prokaryotes were observed in samples filtered through a 5 μm mesh of the in-water cleaning effluent, even at a low fouling rating (Levels 1–2). These experiments suggest a necessity to consider a secondary treatment method in addition to the primary filtration method for the treatment of in-water cleaning effluents.

Surface sediment classification using a deep learning model and unmanned aerial vehicle data of tidal flats - Kye-Lim Kim; Han-Jun Woo; Hyeong-Tae Jou; Hahn Chul Jung; Seung-Kuk Lee; Joo-Hyung Ryu (Marine Pollution Bulletin, 2024)

Multilayer composite membranes composed of carbon molecular sieve membranes sandwiched between stacked zeolite nanosheets - Dong Yun Han; Ah Hyun Lee; Su Kyung Kang; Se Wan Kim; Woo Chul Kwak; In-Seok Jeon; Seunghwa Yang; Pyung Soo Lee (Chemical Engineering Journal, 2024)

On the Species Identification of Korean Geoduck Clam (Panopea sp. 1) Based on the Morphological and Molecular Evidence - Jeonghoon Han; Jong Guk Kim; O-Nam Kwon; Jordan Jun Chul Park; Kyun-Woo Lee; Young-Ung Choi (Journal of Marine Science and Engineering, 2023)
The geoduck clam is a high-value species in South Korea. However, the molecular and morphological characteristics of geoduck clams from the southern coast of South Korea remain unexamined. The accurate identification of native geoduck clams is crucial for their conservation and management. Therefore, this study used a combination of molecular and morphological analyses to characterize native geoduck clams from the southern coast of South Korea. Based on complete mitochondrial genome and morphological analyses, the native species of geoduck clam from this study area was identified as Panopea sp. 1. The complete mitochondrial genome sequencing of Panopea sp. 1 revealed a total of 16,225 bp in length with 37 genes (13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes). It was also shown that Panopea sp. 1 belongs to the family Hiatellidae based on a phylogenetic analysis tree with 11 bivalve species. In particular, Panopea sp. 1 is closely related to three other Panopea species (Panopea sp., Panopea abrupta, and Panopea japonica). The phylogenetic analysis correlated with the morphological analysis. Overall, this is the first reliable record of Panopea sp. 1 in South Korea. These findings provide a basis for accurate species identification based on morphological characteristics and complete mitochondrial genome sequencing.

Macrosphelides from Antarctic fungus Pseudogymnoascus sp. (strain SF-7351) and their neuroprotective effects on BV2 and HT22 cells - Zhiming Liu; Le Ba Vinh; Nguyen Quoc Tuan; Hwan Lee; Eunae Kim; Youn-Chul Kim; Jae Hak Sohn; Joung Han Yim; Ha-Jin Lee; Dong-Sung Lee; Hyuncheol Oh (Chemico-Biological Interactions, 2023)

Recent trends and perspectives of artificial intelligence-based machine learning from discovery to manufacturing in biopharmaceutical industry - Ravi Maharjan; Jae Chul Lee; Kyeong Lee; Hyo-Kyung Han; Ki Hyun Kim; Seong Hoon Jeong (Journal of Pharmaceutical Investigation, 2023)

Localized conditional induction of brain arteriovenous malformations in a mouse model of hereditary hemorrhagic telangiectasia - Lea Scherschinski; Chul Han; Yong Hwan Kim; Ethan A. Winkler; Joshua S. Catapano; Tyler D. Schriber; Peter Vajkoczy; Michael T. Lawton; S. Paul Oh (Angiogenesis, 2023)
Background Longitudinal mouse models of brain arteriovenous malformations (AVMs) are crucial for developing novel therapeutics and pathobiological mechanism discovery underlying brain AVM progression and rupture. The sustainability of existing mouse models is limited by ubiquitous Cre activation, which is associated with lethal hemorrhages resulting from AVM formation in visceral organs. To overcome this condition, we developed a novel experimental mouse model of hereditary hemorrhagic telangiectasia (HHT) with CreER-mediated specific, localized induction of brain AVMs. Methods Hydroxytamoxifen (4-OHT) was stereotactically delivered into the striatum, parietal cortex, or cerebellum of R26 CreER ; Alk1 2f/2f ( Alk1 -iKO) littermates. Mice were evaluated for vascular malformations with latex dye perfusion and 3D time-of-flight magnetic resonance angiography (MRA). Immunofluorescence and Prussian blue staining were performed for vascular lesion characterization. Results Our model produced two types of brain vascular malformations, including nidal AVMs (88%, 38/43) and arteriovenous fistulas (12%, 5/43), with an overall frequency of 73% (43/59). By performing stereotaxic injection of 4-OHT targeting different brain regions, Alk1 -iKO mice developed vascular malformations in the striatum (73%, 22/30), in the parietal cortex (76%, 13/17), and in the cerebellum (67%, 8/12). Identical application of the stereotaxic injection protocol in reporter mice confirmed localized Cre activity near the injection site. The 4-week mortality was 3% (2/61). Seven mice were studied longitudinally for a mean (SD; range) duration of 7.2 (3; 2.3−9.5) months and demonstrated nidal stability on sequential MRA. The brain AVMs displayed microhemorrhages and diffuse immune cell invasion. Conclusions We present the first HHT mouse model of brain AVMs that produces localized AVMs in the brain. The mouse lesions closely resemble the human lesions for complex nidal angioarchitecture, arteriovenous shunts, microhemorrhages, and inflammation. The model’s longitudinal robustness is a powerful discovery resource to advance our pathomechanistic understanding of brain AVMs and identify novel therapeutic targets.

Offshore Wind Farms in South Korea: A Potential Site for Scallop Culture - Dae-Won Lee; Sung-Yong Oh; Jordan Jun Chul Park; Yun-Hwan Jung; Han-Jun Kim; Dong Mun Choi; Young-Ung Choi; Jeonghoon Han (Journal of Marine Science and Engineering, 2023)
Owing to the constant wind generated by the vast ocean, energy production from offshore wind farms (OWFs) plays an important role in the expansion of renewable energy. However, areas close to large wind farms are often left unutilized, and aquaculture farmers find it difficult to efficiently utilize these unoccupied spaces due to limited information showing the feasibility of utilization of OWFs as potential scallop culture sites. To analyze whether the two scallop species Zhikong scallop (Chlamys farreri) and bay scallop (Argopecten irradians) can be grown at OWFs of Gochang and Buan, Jeollabuk-do, Republic of Korea, the growth characteristics of the two scallop species were analyzed and compared with those grown at the Tongyeong Megacosm Test Station. The results clearly showed that the growth of scallops at the OWF was significantly lower with respect to the shell lengths, height, width, and weight, compared to those grown at the megacosm station. However, scallops grown at the OWF still showed consistent growth in parallel with those grown at the megacosm test station. Yet, there was a species-specific mortality rate between the two sites. In addition, our results suggest that temperature may be a key determinant of the growth of C. farreri and A. irradians. Overall, this study contributes to establishing a foundation for the stable and continuous farming of marine bivalves (e.g., clams, oysters, mussels, and scallops) in OWF areas.

Shear Force and Bending Moment Tuning Algorithm of Shuttle Tanker Model for Global Structural Analysis - Chaeog Lim; Ik-seung Han; Ju-Young Kang; Im-jun Ban; Byungkeun Lee; Jun Soo Park; Sung-chul Shin (Journal of Marine Science and Engineering, 2023)
Global ship analysis is conducted using a finite element model (FE model) for ship design and construction, which involves structural, motion, and vibration analyses. It is crucial to examine the structural safety of the hull and motion response. In the ship FE model used in global ship analysis, weight distribution is employed to adjust the light weight and center of gravity (COG), which are required to perform the analysis. Further, the FE model needs to satisfy the required longitudinal shear force (SF) and bending moment (BM) under the loading conditions of the ship. Moreover, the SF and BM in the ship Trim and Stability data are utilized to perform shear force tuning (SFT) and bending moment tuning (BMT) for the ship FE model. This ensures the ship model exhibits curves of the SF and BM that coincide with those of the ship. The SFT and BMT for the ship FE model are time-consuming and costly. Thus, to address these limitations, we propose an effective and accurate algorithm and program for SFT and BMT. Accordingly, we developed a C#-based algorithm to tune the weight, SF, BM, and COG of the ship FE model to the required target value. Finally, the accuracy of the newly developed algorithm was analyzed and compared by applying it to the shuttle tanker FE model under the ballast and full load conditions. Accuracy was within tolerance in both loading conditions. The average errors of SF and BM were smaller in the ballast condition than in the full load condition, and the errors were smaller at the bow than at the stern.

Investigation on the adsorption characteristics of pharmaceuticals and personal care products on polyethylenimine-alginate-activated carbon composite fiber - Se-Been Mun; Minhee Han; Yub Raj Dangi; Bo-Gyeon Cho; Se-Ra Jin; Kwan-Yong Lee; Che-Ryong Lim; Chul-Woong Cho; Yeoung-Sang Yun (Desalination, 2023)

Synthesis of ZIF-67-derived CoS2@graphitic carbon/reduced graphene oxide for supercapacitor application - P. Anil Kumar Reddy; Hyungu Han; Ki Chul Kim; Sungjun Bae (Chemical Engineering Journal, 2023)

Exposure dose and temperature of chlorine on deterioration of thin-film composite membranes for reverse osmosis and nanofiltration - Sun-A An; Cheol-Gyu Park; Jin-San Lee; Seong-Min Cho; Yun Chul Woo; Han-Seung Kim (Chemosphere, 2023)

Improved natural food colorant production in the filamentous fungus Monascus ruber using CRISPR-based engineering - Hye Ree Yoon; Suk Han; Seung Chul Shin; Su Cheong Yeom; Hyo Jin Kim (Food Research International, 2023)

Numerical and Experimental Study on NOx Reduction According to the Load in the SCR System of a Marine Boiler - Jeong-Uk Lee; Sung-Chul Hwang; Seung-Hun Han (Journal of Marine Science and Engineering, 2023)
Numerical analysis and experimental studies were conducted to evaluate the performance of a selective catalytic reduction (SCR) system according to the load of a 1.5-ton marine boiler. There are post-treatment methods for reducing the exhaust gas emitted from ships, such as low-sulfur oil, scrubber, a desulfurization device to remove sulfur oxides (SOx) and particulate matter, an exhaust gas recirculation system, and SCR agents to reduce nitrogen oxides (NOx). Furthermore, there are methods of using eco-friendly natural gas fuels, such as liquefied natural gas (LNG), methanol, liquefied petroleum gas, and ammonia. In the case of LNG, SOx and particulate matter are hardly emitted, and only a small amount of NOx is emitted compared to an internal combustion engine. Therefore, SCR system technology that can remove NOx needs to be applied. As a result of this study, the boiler load increased, and the flow velocity through the outlet decreased. In addition, the NOx emissions of diesel fuel and LNG fuel were reduced by 100% to 0 ppm when the boiler load ratio was 50%. When the load ratio was 75%, the NOx emissions of diesel fuel were reduced by 77.4% to 40 ppm, and those of LNG fuel were reduced by 64.1% to 24 ppm. When the load ratio was 100%, the NOx emissions of diesel fuel were reduced by 66.1% to 60 ppm, and those of LNG fuel were reduced by 47.8% to 24 ppm. In addition, the results of the numerical analysis according to boiler load were almost identical to the experimental results. Finally, this study could design an optimal SCR system through numerical analysis, according to the important parameters of the SCR system.

Performance comparisons of the three data assimilation methods for improved predictability of PM2·5: Ensemble Kalman filter, ensemble square root filter, and three-dimensional variational methods - Uzzal Kumar Dash; Soon-Young Park; Chul Han Song; Jinhyeok Yu; Keiya Yumimoto; Itsushi Uno (Environmental Pollution, 2023)

Correction to: TGFβ1-Induced Transglutaminase-2 Triggers Catabolic Response in Osteoarthritic Chondrocytes by Modulating MMP-13 - Jae-Young Park; Hyun Cheol Bae; Sung Hee Pyo; Myung Chul Lee; Hyuk-Soo Han (Tissue Engineering and Regenerative Medicine, 2023)

Evaluation of dryout region in a heap-like debris bed formed in an APR1400 pre-flooded reactor cavity - Hanbee Na; Ji-Hun Kim; Dong-Ho Shin; Han-Chul Kim; Sok Chul Kim (Annals of Nuclear Energy, 2023)

Seismic airgun sound propagation in shallow water of the East Siberian shelf and its prediction with the measured source signature - Dong-Gyun Han; Sookwan Kim; Martin Landrø; Wuju Son; Dae Hyeok Lee; Young Geul Yoon; Jee Woong Choi; Eun Jin Yang; Yeonjin Choi; Young Keun Jin; Jong Kuk Hong; Sung-Ho Kang; et al. (Frontiers in Marine Science, 2023)
Seismic airgun sound was measured with an autonomous passive acoustic recorder as a function of distance from 18.6 to 164.2 km in shallow water (<70 m) at the continental shelf of the East Siberian Sea in September 2019. The least-square regression curves were derived in the zero-to-peak sound pressure level, sound exposure level, and band level in a frequency range between 10 and 300 Hz using the initial amplitude scaled from the near-field hydrophone data. In addition, propagation modeling based on the parabolic equation with the measured source spectrum was performed for range-dependent bathymetry, and the results were compared with the band level of the measurements. The sediment structure of the measurement area was a thin layer of iceberg-scoured postglacial mud overlying a fast bottom with high density based on grounding events of past ice masses. The observed precursor arrivals, modal dispersion, and rapid decrease in spectrum level at low frequencies can be explained by the condition of the high-velocity sediment. Our results can be applied to studies on the inversion of ocean boundary conditions and measurement geometry and basic data for noise impact assessment.

Evaluation of biogenic emissions from three different vegetation distributions in South Korea - Jinhyeok Yu; Kyung M. Han; Chul H. Song; Kyunghwa Lee; Sojin Lee; Younha Kim; Jung-Hun Woo; Saewung Kim; Armin Wisthaler (Atmospheric Environment, 2023)

Effects of temperature and starvation on life history traits and fatty acid profiles of the Antarctic copepod Tigriopus kingsejongensis - Deok-Seo Yoon; Hyuntae Choi; Alaa El-Din H. Sayed; Kyung-Hoon Shin; Joung Han Yim; Sanghee Kim; Min-Chul Lee; Jae-Seong Lee (Regional Studies in Marine Science, 2023)

Association of long-term exposure to PM2.5 and survival following ischemic heart disease - Jongmin Oh; Sangbum Choi; Changwoo Han; Dong-Wook Lee; Eunhee Ha; Soontae Kim; Hyun-Joo Bae; Wook Bum Pyun; Yun-Chul Hong; Youn-Hee Lim (Environmental Research, 2023)

Geochemistry and zircon U-Pb-Hf isotopes of igneous rocks associated with the Dongnam Fe-Mo skarn deposit, Taebaeksan Basin, South Korea - Il-Hwan Oh; Sang-Mo Koh; Chul-Ho Heo; Bum Han Lee; Jieun Seo; Sang-Gun No; Seong-Jun Cho; Bong Chul Yoo (Geosciences Journal, 2022)

U-Pb ages of detrital zircons in lower Palaeozoic quartzites of the Taebaeksan Basin, eastern Sino–Korean Block: sediment provenance response to relative sea-level changes - Changyoon Lee; Yi Kyun Kwon; Jung Min Yeo; Yoo Jin Kwon; Hyun-Chul Han (International Geology Review, 2021)

Cereblon: promise and challenges for combating human diseases - Hyoung Kyu Kim; Jung Eun Seol; Sang Woo Ahn; Seungje Jeon; Chul-Seung Park; Jin Han (Pflügers Archiv - European Journal of Physiology, 2021)

TGFβ1-Induced Transglutaminase-2 Triggers Catabolic Response in Osteoarthritic Chondrocytes by Modulating MMP-13 - Jae-Young Park; Hyun Cheol Bae; Sung Hee Pyo; Myung Chul Lee; Hyuk-Soo Han (Tissue Engineering and Regenerative Medicine, 2021)

Short-term exposure to air pollution and hospital admission for heart failure among older adults in metropolitan cities: a time-series study - Dong-Wook Lee; Chang-Woo Han; Yun-Chul Hong; Jong-Min Oh; Hyun-Joo Bae; Soontae Kim; Youn-Hee Lim (International Archives of Occupational and Environmental Health, 2021)

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

Tiller Outgrowth in Rice (Oryza sativa L.) is Controlled by OsGT1, Which Acts Downstream of FC1 in a PhyB-Independent Manner - Vikranth Kumar; Sung Hoon Kim; Moch Rosyadi Adnan; Jung Heo; Jin Hee Jeong; Ryza A. Priatama; Jeung Joo Lee; Chul Min Kim; Byoung Il Je; Soon Ju Park; Yuan Hu Xuan; Chang-deok Han (Journal of Plant Biology, 2021)

Aquaculture Farming Effect on Benthic Respiration and Nutrient Flux in Semi-Enclosed Coastal Waters of Korea - Sung-Han Kim; Jae-Seong Lee; Kyung-Tae Kim; Hyung-Chul Kim; Won-Chan Lee; Dongmun Choi; Sang-Hwa Choi; Jae-Hoon Choi; Hyo-Jin Lee; Jae-Hyuk Shin (Journal of Marine Science and Engineering, 2021)
Sediment oxygen demand (SOD) and benthic nutrient fluxes (BNFs) were measured using an in situ benthic chamber at a fish farm (FF), oyster farm (OF), and controls (FF-C and OF-C) to assess the impact of aquaculture activities on organic carbon (OC) and nutrients cycles in coastal waters of Korea. The SOD at FF and OF ranged from 60 ± 2 to 157 ± 3 mmol m−2 d−1 and from 77 ± 14 to 84 ± 16 mmol m−2 d−1, respectively, more than five times those of the control sites. The SOD at farm sites is highly correlated with fish stock and food input, suggesting that excess feed input is an important control factor for OC remineralization. The combined analysis of sediment trap and SOD indicates that most of the deposited OC oxidized in the sediment and/or was laterally transported by the current before being buried in the sediment. The benthic nutrient fluxes at farms ranged from 5.45 to 8.95 mmol N m−2 d−1 for nitrogen and from 0.51 to 1.67 mmol P m−2 d−1 for phosphate, respectively, accounting for 37–270% and 52–804% of the N and P required for primary production in the water column. These results indicate that aquaculture farming may profoundly impact biogeochemical cycles in coastal waters.

Correction to: A Novel Method to Differentiate Tonsil-Derived Mesenchymal Stem Cells In Vitro into Estrogen-Secreting Cells - Hee-Yeon Kim; Younghay Lee; Hee-Soo Yoon; Yu-Hee Kim; Kyung-Ah Cho; So-Youn Woo; Han Su Kim; Bo Young Park; Sung-Chul Jung; Inho Jo; Woo-Jae Park; Joo-Won Park; et al. (Tissue Engineering and Regenerative Medicine, 2021)

A Novel Method to Differentiate Tonsil-Derived Mesenchymal Stem Cells In Vitro into Estrogen-Secreting Cells - Hee-Yeon Kim; Younghay Lee; Hee-Soo Yoon; Yu-Hee Kim; Kyong-A Cho; So-Youn Woo; Han Sun Kim; Bo-Young Park; Sung-Chul Jung; Inho Jo; Woo-Jae Park; Joo-Won Park; et al. (Tissue Engineering and Regenerative Medicine, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Effectiveness of surgical, KF94, and N95 respirator masks in blocking SARS-CoV-2: a controlled comparison in 7 patients - Min-Chul Kim; Seongman Bae; Ji Yeun Kim; Se Yoon Park; Joon Seo Lim; Minki Sung; Sung-Han Kim (Infectious Diseases, 2020)

Predicting Functional Outcome Based on Linked Data After Acute Ischemic Stroke: S-SMART Score - Tae Jung Kim; Ji Sung Lee; Mi-Sun Oh; Ji-Woo Kim; Jae Sun Yoon; Jae-Sung Lim; Chan-Hyuk Lee; Heejung Mo; Han-Yeong Jeong; Yerim Kim; Sang-Hwa Lee; Keun-Hwa Jung; et al. (Translational Stroke Research, 2020)

The Contribution of Small Phytoplankton Communities to the Total Dissolved Inorganic Nitrogen Assimilation Rates in the East/Japan Sea: An Experimental Evaluation - Panthalil S. Bhavya; Jae Joong Kang; Hyo Keun Jang; HuiTae Joo; Jae Hyung Lee; Jang Han Lee; Jung Woo Park; Kwanwoo Kim; Hyung Chul Kim; Sang Heon Lee (Journal of Marine Science and Engineering, 2020)
As a part of Korean-Russian joint expeditions in the East/Japan Sea during 2012 and 2015, a set of total and small (

NH4+ Suppresses NO3–-Dependent Lateral Root Growth and Alters Gene Expression and Gravity Response in OsAMT1 RNAi Mutants of Rice (Oryza sativa) - Vikranth Kumar; Sung Hoon Kim; Ryza A. Priatama; Jin Hee Jeong; Moch Rosyadi Adnan; Bernet Agung Saputra; Chul Min Kim; Byoung Il Je; Soon Ju Park; Ki Hong Jung; Kyung Min Kim; Yuan Hu Xuan; et al. (Journal of Plant Biology, 2020)

Assessment of dosimetric leaf gap correction factor in Mobius3D commissioning affected by couch top - Min Cheol Han; Jihun Kim; Chae-Seon Hong; Kyung Hwan Chang; Su Chul Han; Kwangwoo Park; Dong Wook Kim; Myoung Kyu Park; Yu Yun Noh; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2020)

Stealth Polymer-Coated Graphene Oxide Decorated Mesoporous Titania Nanoplatforms for In Vivo Chemo-Photodynamic Cancer Therapy - Milan Gautam; Biki Gupta; Zar Chi Soe; Kishwor Poudel; Srijan Maharjan; Jee-Heon Jeong; Han-Gon Choi; Sae Kwang Ku; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2020)

Comamonas flocculans sp. nov., a Floc-Forming Bacterium Isolated from Livestock Wastewater - Dong-Hyun Kim; Kook-Il Han; Hae-Jun Kwon; Mi-Gyeong Kim; Young-Guk Kim; Doo-Ho Choi; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jong-Guk Kim (Current Microbiology, 2020)

Adsorptive removal of cationic tricyclic antidepressants using cation-exchange resin - Jong-Won Choi; John Kwame Bediako; Yufeng Zhao; Shuo Lin; Amit Kumar Sarkar; Minhee Han; Myung-Hee Song; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Science and Pollution Research, 2020)

Benthic Respiration and Nutrient Release Associated with Net Cage Fish and Longline Oyster Aquaculture in the Geoje-Tongyeong Coastal Waters in Korea - Sung-Han Kim; Hyung Chul Kim; Sang-Hwa Choi; Won-Chan Lee; Rae-Hong Jung; Jung-Ho Hyun; Suk Hyun Kim; Jae Seong Lee (Estuaries and Coasts, 2020)

Algal endophytes of commercial Chondrus ocellatus (Gigartinaceae, Rhodophyta) from different wild populations in Korea - Xu Gao; Cyr Abel Maranguy Ogandaga; Seo Kyoung Park; Ji Chul Oh; Han Gil Choi (Journal of Applied Phycology, 2020)

Therapeutic targets of vitamin D receptor ligands and their pharmacokinetic effects by modulation of transporters and metabolic enzymes - Min Sik Choi; Yu Chul Kim; Han-Joo Maeng (Journal of Pharmaceutical Investigation, 2020)

Collapse Analysis of ERW Pipe Based on Roll-Forming and Sizing Simulations - Seong-Wook Han; Yeun Chul Park; Soo-Chang Kang; Sungmoon Jung; Ho-Kyung Kim (Journal of Marine Science and Engineering, 2019)
The demand for electric resistance welded (ERW) pipe for deep-water installation has increased, which necessitates a higher degree of accuracy in evaluating the strength of pipe in order to satisfy the design limit state, otherwise referred to as the collapse performance. Since ovality and residual stress governs the collapse performance, an accurate evaluation of these factors is needed. An analytical approach using a three-dimensional finite element method was proposed to simulate the roll-forming and sizing processes in manufacturing ERW pipe. To simulate significant plastic deformation during manufacturing, a nonlinear material model that included the Bauschinger effect was incorporated. The manufacturing of ERW pipe made of API 5L X70 steel was simulated and analyzed for collapse performance. Controlling the ovality of the pipe significantly decreased the amount of pressure that would cause a collapse, whereas the effect of residual stress was minor. These two factors could be improved via the use of a proper sizing ratio.

Sternoclavicular septic arthritis caused by Staphylococcus aureus : excellent results from medical treatment and limited surgery - Young-Rock Jang; Taeeun Kim; Min-Chul Kim; Heung Sup Sung; Mi-Na Kim; Min Jae Kim; Sung Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; Yang Soo Kim; Yong Pil Chong (Infectious Diseases, 2019)

Complete genome sequence and phylogenetic analysis of nosocomial pathogen Acinetobacter nosocomialis strain NCTC 8102 - Bindu Subhadra; Surya Surendran; Bo Ra Lim; Jong-Sung Yim; Dong Ho Kim; Kyungho Woo; Kyudong Han; Man Hwan Oh; Chul Hee Choi (Genes & Genomics, 2019)

Cinnamomum camphora Leaves Alleviate Allergic Skin Inflammatory Responses In Vitro and In Vivo - Na-Jin Kang; Sang-Chul Han; Seok-Hyun Yoon; Jae-Yeop Sim; Young Hee Maeng; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2019)

Repositioning of the antipsychotic drug TFP for sepsis treatment - Jung Hwa Park; Hyun Jin Park; Sung Eun Lee; Young Seob Kim; Gun-Young Jang; Hee Dong Han; In Duk Jung; Kyung Chul Shin; Young Min Bae; Tae Heung Kang; Yeong-Min Park (Journal of Molecular Medicine, 2019)

Multiplex PCR using YeaD and 16S rRNA gene to identify major pathogens in vibriosis of Litopenaeus vannamei - Yeong-Jong Han; Ara Jo; So-Won Kim; Hee-Eun Lee; Young Chul Kim; Hyun Do Jeong; Yung Hyun Choi; Suhkmann Kim; Hee-Jae Cha; Heui-Soo Kim (Genes & Genomics, 2019)

Effects of temperature shifts on life parameters and expression of fatty acid synthesis and heat shock protein genes in temperate and Antarctic copepods Tigriopus japonicus and Tigriopus kingsejongensis - Jeonghoon Han; Min-Chul Lee; Jun Chul Park; Sanghee Kim; Jae-Seong Lee (Polar Biology, 2018)

Impact of biogenic emissions on early summer ozone and fine particulate matter exposure in the Seoul Metropolitan Area of Korea - Hyeon-Kook Kim; Chang-Keun Song; Kyung Man Han; Yang Dam Eo; Chul Han Song; Rokjin Park; Sung-Chul Hong; Sang-Kyun Kim; Jung-Hun Woo (Air Quality, Atmosphere & Health, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Erratum to: Loss of Pericytes in Radiation Necrosis after Glioblastoma Treatments - Soon-Tae Lee; Youngbeom Seo; Ji-Yeon Bae; Kon Chu; Jin Wook Kim; Seung Hong Choi; Tae Min Kim; Il Han Kim; Sung-Hye Park; Chul-Kee Park (Molecular Neurobiology, 2018)

Loss of Pericytes in Radiation Necrosis after Glioblastoma Treatments - Soon-Tae Lee; Youngbeom Seo; Ji-Yeon Bae; Kon Chu; Jin Wook Kim; Seung Hong Choi; Tae Min Kim; Il Han Kim; Sung-Hye Park; Chul-Kee Park (Molecular Neurobiology, 2018)

Virulence properties of uropathogenic Escherichia coli isolated from children with urinary tract infection in Korea - Dong Ho Kim; Bindu Subhadra; Hee Young Kang; Kyungho Woo; Jaeseok Kim; Yeo-Jin Son; Kyung Mok Sohn; Hwa-Jung Kim; Kyudong Han; Man Hwan Oh; Chul Hee Choi (Genes & Genomics, 2018)

Complete genome sequence of uropathogenic Escherichia coli isolate UPEC 26-1 - Bindu Subhadra; Dong Ho Kim; Jaeseok Kim; Kyungho Woo; Kyung Mok Sohn; Hwa-Jung Kim; Kyudong Han; Man Hwan Oh; Chul Hee Choi (Genes & Genomics, 2018)

Diagnostic usefulness of the QuantiFERON-TB gold in-tube test (QFT-GIT) for tuberculous vertebral osteomyelitis - Sungim Choi; Kyung Hwa Jung; Hyo-Ju Son; Seung Hyun Lee; Jung Min Hong; Min Chul Kim; Min Jae Kim; Yong Pil Chong; Heungsup Sung; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (Infectious Diseases, 2018)

Paclitaxel and Erlotinib-co-loaded Solid Lipid Core Nanocapsules: Assessment of Physicochemical Characteristics and Cytotoxicity in Non-small Cell Lung Cancer - Biki Gupta; Bijay Kumar Poudel; Shobha Regmi; Shiva Pathak; Hima Bindu Ruttala; Milan Gautam; Gyeong Jin An; Jee-Heon Jeong; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2018)

Plant synthetic GP4 and GP5 proteins from porcine reproductive and respiratory syndrome virus elicit immune responses in pigs - Chul Han An; Salik Nazki; Sung-Chul Park; Yu Jeong Jeong; Ju Huck Lee; Su-Jin Park; Amina Khatun; Won-Il Kim; Youn-Il Park; Jae Cheol Jeong; Cha Young Kim (Planta, 2018)

IDD10 is Involved in the Interaction between NH4+ and Auxin Signaling in Rice Roots - Yuan Hu Xuan; Vikranth Kumar; Xiao Feng Zhu; Byoung Il Je; Chul Min Kim; Jin Huang; Jun Hyeon Cho; Gihwan Yi; Chang-deok Han (Journal of Plant Biology, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Integration of Bacterial Expansin on Agarolytic Complexes to Enhance the Degrading Activity of Red Algae by Control of Gelling Properties - Da Woon Jeong; Jeong Eun Hyeon; Young-Chul Joo; Sang Kyu Shin; Sung Ok Han (Marine Biotechnology, 2018)

Erratum to "Anti-Inflammatory Effect of 3-Bromo-4,5-Dihydroxybenzaldehyde, a Component of Polysiphonia morrowii, In Vivo and In Vitro " [Toxicol. Res. 33 (2017) 325-332] - Na-Jin Kang; Sang-Chul Han; Hyun-Jae Kang; Geum Ko; Weon-Jong Yoon; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2018)

Distinct Histone Modifications Modulate DEFB1 Expression in Human Vaginal Keratinocytes in Response to Lactobacillus spp. - Jaehyouk Lee; Ara Jang; Jin Wook Kim; Jun Hyun Han; Byung Hee Chun; Hye Su Jung; Che Ok Jeon; Soon Chul Myung (Probiotics and Antimicrobial Proteins, 2017)

(E)-2-Methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) Phenol Ameliorates LPS-Mediated Memory Impairment by Inhibition of STAT3 Pathway - Ji Yeon Choi; Chul Ju Hwang; Do Yeon Lee; Sun Mi Gu; Hee Pom Lee; Dong Young Choi; Ki Wan Oh; Sang-Bae Han; Jin Tae Hong (NeuroMolecular Medicine, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Anti-Inflammatory Effect of 3-Bromo-4,5-Dihydroxybenzaldehyde, a Component of Polysiphonia morrowii , In Vivo and In Vitro - Na-Jin Kang; Sang-Chul Han; Hyun-Jae Kang; Geum Ko; Weon-Jong Yoon; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2017)

Dissipation kinetics, pre-harvest residue limits, and hazard quotient assessments of pesticides flubendiamide and fluopicolide in Korean melon (Cucumis melo L. var. makuwa) grown under regulated conditions in plastic greenhouses - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Sung-Woo Kim; Han Sol Lee; Hyung Suk Chung; Jung Ah Do; Ji Hoon Jeong; Byung-Joon Chang; Moon Ik Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Effects of temperature on growth and fatty acid synthesis in the cyclopoid copepod Paracyclopina nana - Seung-Hwi Lee; Min-Chul Lee; Jayesh Puthumana; Jun Chul Park; Sujin Kang; Jeonghoon Han; Kyung-Hoon Shin; Heum Gi Park; Ae-Son Om; Jae-Seong Lee (Fisheries Science, 2017)

Dissipation pattern and risk quotients assessment of amisulbrom in Korean melon cultivated in plastic house conditions - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Hyung Suk Chung; Han Sol Lee; Sun-Hyang Park; Fazil Hacımüftüoğlu; Byung-Joon Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Monitoring and Assessment, 2017)

Factors predicting life-threatening infections with respiratory syncytial virus in adult patients - Se Yoon Park; Taeeun Kim; Young Rock Jang; Min-Chul Kim; Yong Pil Chong; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim (Infectious Diseases, 2017)

Lacinutrix chionocetis sp. nov., isolated from gut of a red snow crab - Hyangmi Kim; Sang-Chul Yoon; Kwang-Ho Choi; Sung-Tae Kim; Jae-Bong Lee; Dong-Sun Kim; Ho Le Han; Kyung Sook Bae; Doo-Sang Park (Archives of Microbiology, 2017)

Preparation and Optimization of Immediate Release/Sustained Release Bilayered Tablets of Loxoprofen Using Box–Behnken Design - Jin Wook Tak; Biki Gupta; Raj Kumar Thapa; Kyu Bong Woo; Sung Yub Kim; Toe Gyeong Go; Yongjoo Choi; Ju Yeon Choi; Jee-Heon Jeong; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (AAPS PharmSciTech, 2017)

Analysis and optimization of drug solubility to improve pharmacokinetics - Raj Kumar Thapa; Han-Gon Choi; Jong Oh Kim; Chul Soon Yong (Journal of Pharmaceutical Investigation, 2017)

Functional identification of oleate 12-desaturase and ω-3 fatty acid desaturase genes from Perilla frutescens var. frutescens - Kyeong-Ryeol Lee; Yongjik Lee; Eun-Ha Kim; Seul-Bee Lee; Kyung Hee Roh; Jong-Bum Kim; Han-Chul Kang; Hyun Uk Kim (Plant Cell Reports, 2016)

An overview on common aspects influencing the dissipation pattern of pesticides: a review - Waziha Farha; A. M. Abd El-Aty; Md. Musfiqur Rahman; Ho-Chul Shin; Jae-Han Shim (Environmental Monitoring and Assessment, 2016)

Folate-Mediated Targeted Delivery of Combination Chemotherapeutics Loaded Reduced Graphene Oxide for Synergistic Chemo-Photothermal Therapy of Cancers - Raj Kumar Thapa; Yongjoo Choi; Jee-Heon Jeong; Yu Seok Youn; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2016)

Metabolic engineering to produce γ-linolenic acid in Brassica napus using a Δ6-desaturase from pike eel - Sun Hee Kim; Kyung Hee Roh; Kyeong-Ryeol Lee; Han-Chul Kang; Hyun Uk Kim; Jong Bum Kim (Plant Biotechnology Reports, 2016)

Combined phototherapy in anti-cancer treatment: therapeutics design and perspectives - Tuan Hiep Tran; Raj Kumar Thapa; Hanh Thuy Nguyen; Tung Thanh Pham; Thiruganesh Ramasamy; Dong Shik Kim; Chul Soon Yong; Jong Oh Kim; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2016)

A diagnostic algorithm for tuberculous pleurisy using the ELISPOT assay on peripheral blood and pleural effusion - Min-Chul Kim; Sun-Mi Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; Jun Hee Woo; Sung-Han Kim (Infectious Diseases, 2016)

Enhanced production of resveratrol derivatives in tobacco plants by improving the metabolic flux of intermediates in the phenylpropanoid pathway - Yu Jeong Jeong; Chul Han An; Su Gyeong Woo; Ji Hye Park; Ki-Won Lee; Sang-Hoon Lee; Yeonggil Rim; Hyung Jae Jeong; Young Bae Ryu; Cha Young Kim (Plant Molecular Biology, 2016)

Gluconic acid production by gad mutant of Klebsiella pneumoniae - Dexin Wang; Chenhong Wang; Dong Wei; Jiping Shi; Chul Ho Kim; Biao Jiang; Zengsheng Han; Jian Hao (World Journal of Microbiology and Biotechnology, 2016)

Cereblon in health and disease - Hyoung Kyu Kim; Tae Hee Ko; Bayalagmaa Nyamaa; Sung Ryul Lee; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Chul-Seung Park; Bernd Nilius; Jin Han (Pflügers Archiv - European Journal of Physiology, 2016)

Inhibition of c-Yes induces differentiation of HT-29 human colon cancer stem cells through midbody elongation - Jessica Jung; Sung Chul Choi; Han-Na Lee; Gi-Yeon Han; Chan-Wha Kim (Tissue Engineering and Regenerative Medicine, 2016)

Development of novel tetra- and trinucleotide microsatellite markers for giant grouper Epinephelus lanceolatus using 454 pyrosequencing - Keun-Sik Kim; Choong Hwan Noh; Shin-Joo Moon; Seung-Hee Han; In-Chul Bang (Molecular Biology Reports, 2016)

A combined liquid chromatography-triple-quadrupole mass spectrometry method for the residual detection of veterinary drugs in porcine muscle, milk, and eggs - Dan Zhang; Zee-Yong Park; Jin-A Park; Seong-Kwan Kim; Daun Jeong; Sang-Hyun Cho; Jae-Han Shim; Jin-Suk Kim; A. M. Abd El-Aty; Ho-Chul Shin (Environmental Monitoring and Assessment, 2016)

Effects of Formulation Variables on the Particle Size and Drug Encapsulation of Imatinib-Loaded Solid Lipid Nanoparticles - Biki Gupta; Bijay Kumar Poudel; Shiva Pathak; Jin Wook Tak; Hee Hyun Lee; Jee-Heon Jeong; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (AAPS PharmSciTech, 2016)

External Application of Apo-9'-fucoxanthinone, Isolated from Sargassum muticum, Suppresses Inflammatory Responses in a Mouse Model of Atopic Dermatitis - Sang-Chul Han; Na-Jin Kang; Weon-Jong Yoon; Sejin Kim; Min-Chull Na; Young-Sang Koh; Jin-Won Hyun; Nam-Ho Lee; Mi-Hee Ko; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2016)

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4 - Kang-In Lee; Han-Gyu Choi; Yeo-Jin Son; Jake Whang; Kwangwook Kim; Heat Sal Jeon; Hye-Soo Park; Yong Woo Back; Seunga Choi; Seong-Woo Kim; Chul Hee Choi; Hwa-Jung Kim (Apoptosis, 2016)

Development of Solid Self-Emulsifying Formulation for Improving the Oral Bioavailability of Erlotinib - Duy Hieu Truong; Tuan Hiep Tran; Thiruganesh Ramasamy; Ju Yeon Choi; Hee Hyun Lee; Cheol Moon; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (AAPS PharmSciTech, 2016)

Transcription factor Sp1 prevents TRF2ΔBΔM-induced premature senescence in human diploid fibroblasts - Hyun Ju An; Hyeon Ju Lee; Suhwa Jang; Yu-Jin Jung; Sun Shim Choi; Sang Chul Park; Jeong A. Han (Molecular and Cellular Biochemistry, 2016)

Effects of light shading and climatic conditions on the metabolic behavior of flonicamid in red bell pepper - Da-I Jung; Waziha Farha; A. M. Abd El-Aty; Sung-Woo Kim; Md. Musfiqur Rahman; Jeong-Heui Choi; Md. Humayun Kabir; So Jeong Im; Young-Jun Lee; Lieu. T. B. Truong; Ho-Chul Shin; Geon-Jae Im; et al. (Environmental Monitoring and Assessment, 2016)

Protective effect of a freshwater alga, Spirogyra sp., against lipid peroxidation in vivo zebrafish and purification of antioxidative compounds using preparative centrifugal partition chromatography - Ji-Hyeok Lee; Jong Won Han; Ju-Young Ko; Wonwoo Lee; Ginnae Ahn; Chul-Young Kim; Gwang Hoon Kim; You-Jin Jeon (Journal of Applied Phycology, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Analysis of DDT and its metabolites in soil and water samples obtained in the vicinity of a closed-down factory in Bangladesh using various extraction methods - M. N. U. Al Mahmud; Farzana Khalil; Md. Musfiqur Rahman; M. I. R. Mamun; Mohammad Shoeb; A. M. Abd El-Aty; Jong-Hyouk Park; Ho-Chul Shin; Nilufar Nahar; Jae-Han Shim (Environmental Monitoring and Assessment, 2015)

A transcriptomic analysis of the response of the arctic pteropod Limacina helicina to carbon dioxide-driven seawater acidification - Hye Yeon Koh; Jun Hyuck Lee; Se Jong Han; Hyun Park; Seung Chul Shin; Sung Gu Lee (Polar Biology, 2015)

Modulation of Pharmacokinetic and Cytotoxicity Profile of Imatinib Base by Employing Optimized Nanostructured Lipid Carriers - Biki Gupta; Bijay Kumar Poudel; Tuan Hiep Tran; Roshan Pradhan; Hyuk-Jun Cho; Jee-Heon Jeong; Beom Soo Shin; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2015)

Cold adaptation of a psychrophilic chaperonin from Psychrobacter sp. and its application for heterologous protein expression - Han-Woo Kim; Ah Ram Wi; Byoung Wook Jeon; Jun Hyuck Lee; Seung Chul Shin; Hyun Park; Sung-Jong Jeon (Biotechnology Letters, 2015)

Neuroinflammatory and Amyloidogenic Activities of IL-32β in Alzheimer’s Disease - Hyung-Mun Yun; Jin A. Kim; Chul Ju Hwang; Peng Jin; Myung Ki Baek; Jin Moo Lee; Ji Eun Hong; Sang Min Lee; Sang Bae Han; Ki Wan Oh; Dong Young Choi; Do Young Yoon; et al. (Molecular Neurobiology, 2015)

Memory Impairment in Estrogen Receptor α Knockout Mice Through Accumulation of Amyloid-β Peptides - Chul Ju Hwang; Hyung-Mun Yun; Kyung-Ran Park; Ju Kyung Song; Hyun Ok Seo; Byung Kook Hyun; Dong Young Choi; Hwan-Soo Yoo; Ki-Wan Oh; Dae Yeun Hwang; Sang-Bae Han; Jin Tae Hong (Molecular Neurobiology, 2015)

Polypeptide-based Micelles for Delivery of Irinotecan: Physicochemical and In vivo Characterization - Thiruganesh Ramasamy; Ju Yeon Choi; Hyuk Jun Cho; Subbaih Kandasamy Umadevi; Beom Soo Shin; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2015)

Identification of insulin-like peptide 1 (ILP1) gene and its expression in response to different food sources in the intertidal copepod Tigriopus japonicus - Min Chul Lee; Eun-Ji Won; Seung-Hwi Lee; Dae-Sik Hwang; Hui-Su Kim; Jeonghoon Han; Jae-Sung Rhee; Ae-Son Om; Jae-Seong Lee (Fisheries Science, 2015)

Reducing Effect of IL-32α in the Development of Stroke Through Blocking of NF-κB, but Enhancement of STAT3 Pathways - Chul Ju Hwang; Hyung-Mun Yun; Yu Yeon Jung; Dong Hun Lee; Na Young Yoon; Hyun Ok Seo; Jin-Yi Han; Ki-Wan Oh; Dong Young Choi; Sang-Bae Han; Do Young Yoon; Jin Tae Hong (Molecular Neurobiology, 2015)

Preparation and Characterization of Fenofibrate-Loaded Nanostructured Lipid Carriers for Oral Bioavailability Enhancement - Tuan Hiep Tran; Thiruganesh Ramasamy; Duy Hieu Truong; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (AAPS PharmSciTech, 2014)

Mapping of QTL for yield and its related traits in a doubled haploid population of Korean wheat - Han Sol Lee; Ji-Ung Jung; Chon-Sik Kang; Hwa-Young Heo; Chul Soo Park (Plant Biotechnology Reports, 2014)

VEGF neutralization can prevent and normalize arteriovenous malformations in an animal model for hereditary hemorrhagic telangiectasia 2 - Chul Han; Se-woon Choe; Yong Hwan Kim; Abhinav P. Acharya; Benjamin G. Keselowsky; Brian S. Sorg; Young-Jae Lee; S. Paul Oh (Angiogenesis, 2014)

Coexpression of multiple genes reconstitutes two pathways of very long-chain polyunsaturated fatty acid biosynthesis in Pichia pastoris - Sun Hee Kim; Kyung Hee Roh; Kwang-Soo Kim; Hyun Uk Kim; Kyeong-Ryeol Lee; Han-Chul Kang; Jong-Bum Kim (Biotechnology Letters, 2014)

Isolation and characterization of 26 novel polynucleotide microsatellites from short barbeled grunter (Hapalogenys nitens) for genetic analysis - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Development of Vorinostat-Loaded Solid Lipid Nanoparticles to Enhance Pharmacokinetics and Efficacy against Multidrug-Resistant Cancer Cells - Tuan Hiep Tran; Thiruganesh Ramasamy; Duy Hieu Truong; Beom Soo Shin; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2014)

Over-expression of PsGPD, a mushroom glyceraldehyde-3-phosphate dehydrogenase gene, enhances salt tolerance in rice plants - Jung-Il Cho; Hye-Min Lim; Zamin Shaheed Siddiqui; Sung-Han Park; A-Ram Kim; Taek-Ryoun Kwon; Seong-Kon Lee; Soo-Chul Park; Mi-Jeong Jeong; Gang-Seob Lee (Biotechnology Letters, 2014)

Population genetic structure of the tongue sole (Cynoglossus semilaevis) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Marine polyphenol phlorotannins promote non-rapid eye movement sleep in mice via the benzodiazepine site of the GABAA receptor - Suengmok Cho; Minseok Yoon; Ae Nim Pae; Young-Ho Jin; Nam-Chul Cho; Yohko Takata; Yoshihiro Urade; Sojin Kim; Jin-Soo Kim; Hyejin Yang; Jiyoung Kim; Jinkyoung Kim; et al. (Psychopharmacology, 2014)

Chitosan-Based Polyelectrolyte Complexes as Potential Nanoparticulate Carriers: Physicochemical and Biological Characterization - Thiruganesh Ramasamy; Tuan Hiep Tran; Hyuk Jun Cho; Jeong Hwan Kim; Yong Il Kim; Jae Yoon Jeon; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2014)

Proteomic analysis of the effect of retinoic acids on the human breast cancer cell line MCF-7 - Abu Hena Mostafa Kamal; Baek Soo Han; Jong-Soon Choi; Kun Cho; Sun Young Kim; Won Kon Kim; Sang Chul Lee; Kwang-Hee Bae (Molecular Biology Reports, 2014)

Physiological mechanism of drought tolerance in transgenic rice plants expressing Capsicum annuum methionine sulfoxide reductase B2 (CaMsrB2) gene - Zamin Shaheed Siddiqui; Jung-Il Cho; Taek-Ryoun Kwon; Byung-Ok Ahn; Kang-Seob Lee; Mi-Jeong Jeong; Tae-Hun Ryu; Seong-Kon Lee; Soo-Chul Park; Sung-Han Park (Acta Physiologiae Plantarum, 2014)

Liquid chromatography–tandem mass spectrometry for quantification of cefaclor in rat plasma and its application to pharmacokinetic studies - Hyo-Eon Jin; Yu Chul Kim; Han-Joo Maeng (Journal of Pharmaceutical Investigation, 2014)

Identification and functional characterization of polyunsaturated fatty acid elongase (McELOVL5) gene from pike eel (Muraenesox cinereus) - Sun Hee Kim; So Yun Kim; Eui Ki Kim; Kyung Hee Roh; Jung-Bong Kim; Kwang-Soo Kim; Hyun Uk Kim; Kyeong-Ryeol Lee; Han-Chul Kang; Jong-Sug Park; Kyung Hyun Kim; Jong-Bum Kim (Biotechnology Letters, 2014)

Meeting report: Frontiers in genetics: genomics and epigenomics - Kyudong Han; Chul Geun Kim; Nam-Soo Kim (Genes & Genomics, 2013)

Effects of chronic social defeat stress on behavior and choline acetyltransferase, 78-kDa glucose-regulated protein, and CCAAT/enhancer-binding protein (C/EBP) homologous protein in adult mice - Tong Zhao; Guang-Biao Huang; Sushma Shrestha Muna; Tarique Rajasaheb Bagalkot; Hong-Mei Jin; Han-Jung Chae; Young-Chul Chung (Psychopharmacology, 2013)

Docetaxel-Loaded Thermosensitive and Bioadhesive Nanomicelles as a Rectal Drug Delivery System for Enhanced Chemotherapeutic Effect - Youn Gee Seo; Dong-Wuk Kim; Woo Hyun Yeo; Thiruganesh Ramasamy; Yu-Kyoung Oh; Young-Joon Park; Jung-Ae Kim; Dong Hoon Oh; Sae Kwang Ku; Jin Ki Kim; Chul Soon Yong; Jong Oh Kim; et al. (Pharmaceutical Research, 2013)

Formin homology 1 (OsFH1) regulates root-hair elongation in rice (Oryza sativa) - Jin Huang; Chul Min Kim; Yuan-hu Xuan; Jingmiao Liu; Tae Ho Kim; Bo-Kyeong Kim; Chang-deok Han (Planta, 2013)

OsSNDP1, a Sec14-nodulin domain-containing protein, plays a critical role in root hair elongation in rice - Jin Huang; Chul Min Kim; Yuan-hu Xuan; Soon Ju Park; Hai Long Piao; Byoung Il Je; Jingmiao Liu; Tae Ho Kim; Bo-Kyeong Kim; Chang-Deok Han (Plant Molecular Biology, 2013)

Abnormal liver differentiation and excessive angiogenesis in mice lacking Runx3 - Jong-Min Lee; Dong-Joon Lee; Suk-Chul Bae; Han-Sung Jung (Histochemistry and Cell Biology, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Wound healing evaluation of benzalkonium chloride-loaded hydrocolloid in the wound infection model - Jeong Hwan Kim; Sung Giu Jin; Sae Kwang Ku; Doo Hyun Nam; Young Taek Sohn; Dong Sung Ryu; Eui-Seon Do; Sun Woo Jang; Mi Woon Son; Chul Soon Yong; Han-Gon Choi; Jong Oh Kim (Journal of Pharmaceutical Investigation, 2012)

AMPK activation reduces vascular permeability and airway inflammation by regulating HIF/VEGFA pathway in a murine model of toluene diisocyanate-induced asthma - Seoung Ju Park; Kyung Sun Lee; So Ri Kim; Han Jung Chae; Wan Hee Yoo; Dong Im Kim; Myoung Shin Jeon; Yong Chul Lee (Inflammation Research, 2012)

Pollen allergic risk assessment of genetically modified virus resistant pepper and functional Chinese cabbage - Ju Suk Lee; Ye-Jin Kim; Ki-Hyun Ryu; Tae-Ho Han; Kuen-Woo Park; Kyu Hwan Chung; Chan Lee; Gung-Pyo Lee; Sun-Hyung Kim; Jin-Sung Hong; Young-Doo Park; Eun-Taeck Woo; et al. (Horticulture, Environment, and Biotechnology, 2012)

A budget analysis of NO x column losses over the Korean peninsula - Kyung Man Han; Chul Han Song (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Aerosol properties at gosan in Korea during two pollution episodes caused by contrasting weather conditions - Jin Young Kim; Sang-Woo Kim; Young Sung Ghim; Chul Han Song; Soon-Chang Yoon (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Blue LED and succinic acid enhance the growth of Rhodobacter sphaeroides - Hyun Jeong Lee; Ju-Yong Park; Chul-Hee Han; Suk-Tai Chang; Yang-Hoon Kim; Jiho Min (World Journal of Microbiology and Biotechnology, 2011)

Apoptosis of human fibrosarcoma HT-1080 cells by epigallocatechin-3-O-gallate via induction of p53 and caspases as well as suppression of Bcl-2 and phosphorylated nuclear factor-κB - Mi Hee Lee; Dong-Wook Han; Suong-Hyu Hyon; Jong-Chul Park (Apoptosis, 2011)

Gamma-irradiation depletes endogenous germ cells and increases donor cell distribution in chimeric chickens - Kyung Je Park; Seok Jin Kang; Tae Min Kim; Young Mok Lee; Hyung Chul Lee; Gwonhwa Song; Jae Yong Han (In Vitro Cellular & Developmental Biology - Animal, 2010)

Cytoskeletal changes during nuclear and cell division in the freshwater alga Zygnema cruciatum (Chlorophyta, Zygnematales) - Min-Chul Yoon; Jong-Won Han; Mi-Sook Hwang; Gwang-Hoon Kim (Algae, 2010)

OsPRA1 plays a significant role in targeting of OsRab7 into the tonoplast via the prevacuolar compartment during vacuolar trafficking in plant cells - Jae Bok Heo; Woo Young Bang; Se Won Kim; Sung Min Hwang; Young Sim Son; Chak Han Im; Biswa R. Acharya; Chul Wook Kim; Sam Woong Kim; Byung Hyun Lee; Jeong Dong Bahk (Planta, 2010)

Lung tissue regeneration after induced injury in Runx3 KO mice - Jong-Min Lee; Hyuk-Jae Kwon; Suk-Chul Bae; Han-Sung Jung (Cell and Tissue Research, 2010)

Gentamicin-Loaded Wound Dressing With Polyvinyl Alcohol/Dextran Hydrogel: Gel Characterization and In Vivo Healing Evaluation - Ma-Ro Hwang; Jong Oh Kim; Jeong Hoon Lee; Yong Il Kim; Jeong Hoon Kim; Sun Woo Chang; Sung Gju Jin; Jung Ae Kim; Won Seok Lyoo; Sung Soo Han; Sae Kwang Ku; Chul Soon Yong; et al. (AAPS PharmSciTech, 2010)

Actin Microfilament Involved in Regulation of Pacemaking Activity in Cultured Interstitial Cells of Cajal from Murine Intestine - Zuo Yu Wang; Yan Fei Han; Xu Huang; Hong Li Lu; Xin Guo; Yong Chul Kim; Wen Xie Xu (The Journal of Membrane Biology, 2010)

Oligometastases confined one organ from colorectal cancer treated by SBRT - Jin-Kyu Kang; Mi-Sook Kim; Jin Ho Kim; Seong Yul Yoo; Chul Koo Cho; Kwang Mo Yang; Hyung Jun Yoo; Young Seok Seo; Dong Han Lee; Hae Jin Kang; Young Han Kim; Ui-Sup Shin (Clinical & Experimental Metastasis, 2010)

Active reassortment of H9 influenza viruses between wild birds and live-poultry markets in Korea - Ho Jin Moon; Min Suk Song; Deu John M. Cruz; Kuk Jin Park; Philippe Noriel Q. Pascua; Jun Han Lee; Yun Hee Baek; Dong Ho Choi; Young Ki Choi; Chul Joong Kim (Archives of Virology, 2010)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

Low contribution of BRCA1/2 genomic rearrangement to high-risk breast cancer in the Korean population - Moon-Woo Seong; Sung Im Cho; Dong-Young Noh; Wonshik Han; Sung-Won Kim; Chul-Min Park; Hyun-Woong Park; So Yeon Kim; Ji Yeon Kim; Sung Sup Park (Familial Cancer, 2009)

Adaptive response to GSH depletion and resistance to l-buthionine-(S,R)-sulfoximine: involvement of Nrf2 activation - Hyang-Rim Lee; Jeong-Min Cho; Dong-ha Shin; Chul Soon Yong; Han-Gon Choi; Nobunao Wakabayashi; Mi-Kyoung Kwak (Molecular and Cellular Biochemistry, 2008)

Dual knockdown of p65 and p50 subunits of NF-kappaB by siRNA inhibits the induction of inflammatory cytokines and significantly enhance apoptosis in human primary synoviocytes treated with tumor necrosis factor-alpha - Ui Jin Lee; So-Rim Choung; K. V. Bhanu Prakash; Eun-Ju Lee; Mi Young Lee; Young Joo Kim; Chang-Whan Han; Young-Chul Choi (Molecular Biology Reports, 2008)

Comparative stomach contents and growth of the juvenile black rockfish Sebastes inermis reared in illuminated and unilluminated cages - Ho-Seop YOON; Chul-Won PARK; Sung-Yong MOON; Kyeong-Ho HAN; Hae-Lip SUH; Yun-Keun AN; Sang-Duk CHOI (Fisheries Science, 2008)

Expressional characterization of dehydroascorbate reductase cDNA in transgenic potato plants - Young-Min Goo; Hyun Jin Chun; Tae-Won Kim; Cheol-Ho Lee; Mi-Jeong Ahn; Shin-Chul Bae; Kang-Jin Cho; Jae-An Chun; Chung-Han Chung; Shin-Woo Lee (Journal of Plant Biology, 2008)

A Ds-insertion mutant of OSH6 (Oryza sativa Homeobox 6) exhibits outgrowth of vestigial leaf-like structures, bracts, in rice - Sung Han Park; Chul Min Kim; Byoung Il Je; Su Hyun Park; Soon Ju Park; Hai Long Piao; Yuan-hu Xuan; Mi Sook Choe; Kouji Satoh; Shoshi Kikuchi; Kon Ho Lee; Young Soon Cha; et al. (Planta, 2007)

Analysis of gene-trap Ds rice populations in Korea - Sung Han Park; Nam Soo Jun; Chul Min Kim; Tae Yong Oh; Jin Huang; Yuan-hu Xuan; Soon Ju Park; Byoung Il Je; Hai Long Piao; Soo Hyun Park; Young Soon Cha; Byung Ohg Ahn; et al. (Plant Molecular Biology, 2007)

3D gravity modelling for Anyongbok Seamount in the East Sea - Moo Hee Kang; Hyun-Chul Han; Hyesu Yun; Gee Soo Kong; Kyong O. Kim; Youn Soo Lee (Marine Geophysical Research, 2007)

Identification and Isolation of Differentially Expressed Gene in Response to Cold Stress in a Green Alga, Spirogyra varians (Zygnematales) - Jong-Won Han; Min-Chul Yoon; Key-Pyoung Lee; Gwang-Hoon Kim (Algae, 2007)

Isolation of Total RNA from a Freshwater Green Alga, Zygnema cruciatum, Containing High Levels of Pigments - Jong-Won Han; Min-Chul Yoon; Key-Pyoung Lee; Gwang-Hoon Kim (Algae, 2007)

Population Genetic Structure of the Ark Shell Scapharca broughtonii Schrenck from Korea, China, and Russia Based on COI Gene Sequences - Eun-Seob Cho; Choon-Goon Jung; Sang-Gyu Sohn; Chul-Won Kim; Seock-Jung Han (Marine Biotechnology, 2007)

Geochemical characterization of the organic matter, pore water constituents and shallow methane gas in the eastern part of the Ulleung Basin, East Sea (Japan Sea) - Ji‐Hoon Kim; Myong‐Ho Park; Urumu Tsunogai; Tae‐Jin Cheong; Byong‐Jae Ryu; Young‐Joo Lee; Hyun‐Chul Han; Jae‐Ho Oh; Ho‐Wan Chang (Island Arc, 2007)
Geochemical analyses of sediments, pore water and headspace gas of the piston cores taken from the eastern part of Ulleung Basin of the East Sea (Japan Sea) were carried out to assess the origin of the sedimentary organic matter and interstitial fluid. Several tephra layers within the core are identified as the Ulleung‐Oki (10.1 ka), the Aira‐Tanzawa (23 ka) and the Ulleung‐Yamato (30.9 ka) tephras. With the exception of these volcanic layers, the cores consist predominantly of muddy sediments that contain >0.5% total organic carbon. Atomic C/N ratios and δ 13 C org values suggest that the organic matter originated from marine algae rather than from land vascular plants, whereas Rock‐Eval pyrolysis suggests that the organic matter is thermally immature and comes from a land vascular plant (Type III). These conflicting results seem to be caused by the heavy oxidization of the marine organic matter. Sulphate concentration profiles of pore waters show strongly linear depletion ( r 2 > 0.97) with sediment depth. The estimated sulphate–methane interface (SMI) depth using the sulphate concentration gradient was nearly 3.5 m below seafloor (mbsf) in the southern part of the study area, and deeper than 6 mbsf in the northern part of the area. The difference in SMI depths is likely associated with the amount of the methane flux. The methane concentration below the SMI in the two southern cores increases rapidly, implying the occurrence of methanogenesis and anaerobic methane oxidation (AMO). In contrast, the two northern cores have a low methane concentration below the SMI. values measured from all cores were in the range of −83.5 to −69.5‰, which suggests that the methane derives from a methanogenic microbe. values become decreased toward SMI, but increased below SMI; therefore, has eventually the minimum value near the SMI. The values are also decreased when the methane concentration is increased. These phenomena support the typical occurrence of AMO in the study area.

Comparative expression and characterization of dehydroascorbate reductase cDNA from transformed sesame hairy roots using real-time RT-PCR - Jae An Chun; Jee Young Seo; Mi Ok Han; Jin Woo Lee; Young Byung Yi; Gun Yong Park; Shin Woo Lee; Shin Chul Bae; Kang Jin Cho; Chung Han Chung (Journal of Plant Biology, 2006)

Using canopy reflectance and partial least squares regression to calculate within-field statistical variation in crop growth and nitrogen status of rice - Hung T. Nguyen; Jun Han Kim; Anh T. Nguyen; Lan T. Nguyen; Jin Chul Shin; Byun-Woo Lee (Precision Agriculture, 2006)

Differential expression of rice lipid transfer protein gene(LTP) classes in response to abscisic acid, salt, salicylic acid, and the fungal pathogenMagnaporthe grisea - Tae Hyun Kim; Moon Chul Kim; Jong Ho Park; Seong Sook Han; Byung Ryun Kim; Byoung Yong Moon; Mi Chung Suh; Sung Ho Cho (Journal of Plant Biology, 2006)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

The use of Silver-coated Ceramic Beads for Sterilization of Sphingomonas sp. in Drinking Mineral Water - Dong-Wook Han; Min Sub Lee; Mi Hee Lee; Masakazu Uzawa; Jong-Chul Park (World Journal of Microbiology and Biotechnology, 2005)

Agrobacterium-mediated transformation of Perilla (Perilla frutescens) - Byoung-Kyu Lee; Seung-Hee Yu; Yul-Ho Kim; Byung-Ohg Ahn; Han-Sun Hur; Sang-Chul Lee; Zhanyuan Zhang; Jang-Yong Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Protection of osteoblastic cells from freeze/thaw cycle-induced oxidative stress by green tea polyphenol - Dong-Wook Han; Hak Hee Kim; Mi Hee Lee; Hyun Sook Baek; Kwon-Yong Lee; Suong-Hyu Hyon; Jong-Chul Park (Biotechnology Letters, 2005)

Exposure to air pollution and pulmonary function in university students - Yun-Chul Hong; Jong-Han Leem; Kwan-Hee Lee; Dong-Hyun Park; Jae-Yeon Jang; Sun-Tae Kim; Eun-Hee Ha (International Archives of Occupational and Environmental Health, 2005)

Enhanced neurite outgrowth of rat neural cortical cells on surface-modified films of poly(lactic-co-glycolic acid) - Dong-Wook Han; Min Sub Lee; Bong Joo Park; Jeong Koo Kim; Jong-Chul Park (Biotechnology Letters, 2005)

Overexpression of human erythropoietin (EPO) affects plant morphologies: retarded vegetative growth in tobacco and male sterility in tobacco and Arabidopsis - Ban Yoon Cheon; Hae Jin Kim; Kyung Hee Oh; Sung Chul Bahn; Ji Hoon Ahn; Jang Won Choi; Sung Han Ok; Jung Myung Bae; Jeong Sheop Shin (Transgenic Research, 2004)

Chitosan sponges as tissue engineering scaffolds for bone formation - Yang-Jo Seol; Jue-Yeon Lee; Yoon-Jeong Park; Yong-Moo Lee; Young -Ku; In-Chul Rhyu; Seung-Jin Lee; Soo-Boo Han; Chong-Pyoung Chung (Biotechnology Letters, 2004)

Studies on the mobilization of a maize transposable family,Ac/Ds, in pepper using In Vivo transient assay system - Chul Min Kim; Byoung Il Je; Ja Choon Koo; Hai Long Piao; Soon Ju Park; Joo Mi Jeon; Min Kyoung Kim; Sung Han Park; Jin Young Park; Eun Jin Lee; Woo Sik Chung; Kon Ho Lee; et al. (Journal of Plant Biology, 2004)

Cloning and Expression of Pyrroloquinoline Quinone (PQQ) Genes from a Phosphate-Solubilizing Bacterium Enterobacter intermedium - Chul Hong Kim; Song Hee Han; Kil Yong Kim; Baik Ho Cho; Yong Hwan Kim; Bon Sung Koo; Young Cheol Kim (Current Microbiology, 2003)

Antigenicity of the region encoded by exon8 of the human serine protease, HtrA2/Omi, is associated with its protein solubility - Hyo-Jin Park; Ju-Youn Choi; Young-Mo Seong; Chul Han; Sung-Joo Kim Yoon; Seongman Kang; Hyangshuk Rhim (Biotechnology Letters, 2003)

Genomic Cloning of Mud Loach Misgurnus mizolepis (Cypriniformes, Cobitidae) ?-Actin Gene and Usefulness of Its Promoter Region for Fish Transgenesis - Jae Koo Noh; Kyu-Nam Cho; Eun Hwa Han; AeRi Kim; Jae-Seong Lee; Dong Soo Kim; Chul Geun Kim (Marine Biotechnology, 2003)

Effects of salicylic acid on paraquat tolerance inArabidopsis thaliana plants - Hye-Sook Kim; Chang-Jin Lim; Joon-Chul Kim; Chang-Duck Jin; Tae-Jin Han (Journal of Plant Biology, 2003)

Stereochemical control in diastereoselective reduction of α-substituted-β-ketoesters using a reductase purified from Kluyveromyces marxianus - Joo Hwan Cha; Ae Nim Pae; Kyung Il Choi; Yong Seo Cho; Wook Hyun Kim; Ye Sun Han; Hong-Chul Yun; Jongsoo Lee; Hun Yeong Koh; Eun Lee (Biotechnology Letters, 2002)

Comparison of characteristics of levan produced by different preparations of levansucrase from Zymomonas mobilis - Ki-Hyo Jang; Ki-Bang Song; Chul Ho Kim; Bong Hyun Chung; Soon Ah Kang; Uck-Han Chun; Ryo Won Choue; Sang-Ki Rhee (Biotechnology Letters, 2001)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Embryo lethality and teratogenicity of a new fluoroquinolone antibacterial DW-116 in rats - Jong-Choon Kim; Hyo-In Yun; Ho-Chul Shin; Sang-Seop Han; Moon-Koo Chung (Archives of Toxicology, 2000)

Changes in the isozyme composition of antioxidant enzymes in response to aminotriazole in leaves ofArabidopsis thaliana - Kyong-Suk Kang; Chang-Jin Lim; Tae-Jin Han; Joon-Chul Kim; Chang-Duck Jin (Journal of Plant Biology, 1999)

An f-type thioredoxin fromArabidopsis thaliana Leaves - Kim Tae-Soo; Joon Chul Kim; Chang Duck Jin; Tae Jin Han; Chang -Jin Lim (Journal of Plant Biology, 1998)

Activation of ascorbate-glutathione cycle inArabidopsis leaves in response to aminotriazole - Kyong-Suk Kang; Chang-Jin Lim; Tae-Jin Han; Joon-Chul Kim; Chang-Duck Jin (Journal of Plant Biology, 1998)